Constitutive elasto-plastic model for fine soils in the unsaturated to saturated saturation zone. (July 2019) - Fabbri, A.; Wong, H.K.K.; Lai, B.; Bui, T.A.; Branque, D.
Abstract: Near saturation, air bubbles and pockets can be trapped in the porous network of soils. The aim of this paper was to present a coupled model that takes into account the effect of this entrapped air on the poro-elasto-plastic behavior of the soil. The model takes into account the physical-mechanical interactions between different phases as well as the kinematics of each constituent (liquid water, dissolved air, gaseous air and solid grains). This new model was implemented in a FEM code. Some numerical simulations were performed to demonstrate its ability to reproduce a continuous transition of unsaturated to saturated states.